2014
DOI: 10.1242/dev.113969
|View full text |Cite
|
Sign up to set email alerts
|

RBPJ in mouse Sertoli cells is required for proper regulation of the testis stem cell niche

Abstract: Stem cells are influenced by their surrounding microenvironment, or niche. In the testis, Sertoli cells are the key niche cells directing the population size and differentiation fate of spermatogonial stem cells (SSCs). Failure to properly regulate SSCs leads to infertility or germ cell hyperplasia. Several Sertoli cell-expressed genes, such as Gdnf and Cyp26b1, have been identified as being indispensable for the proper maintenance of SSCs in their niche, but the pathways that modulate their expression have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 46 publications
3
64
0
1
Order By: Relevance
“…Based on the earlier findings, Notch signaling in Sertoli cells seems to be activated predominantly by ligands expressed in neighboring germ cells (Garcia et al ., ). Indeed, we found that the exposure of Sertoli cells to each of immobilized ligands (DLL1, DLL4, or JAG1) induced Notch signaling activation as evidenced by increased NICD level and target genes ( Hey1 , Hes5 ) expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the earlier findings, Notch signaling in Sertoli cells seems to be activated predominantly by ligands expressed in neighboring germ cells (Garcia et al ., ). Indeed, we found that the exposure of Sertoli cells to each of immobilized ligands (DLL1, DLL4, or JAG1) induced Notch signaling activation as evidenced by increased NICD level and target genes ( Hey1 , Hes5 ) expressions.…”
Section: Discussionmentioning
confidence: 99%
“…RBPJ acts as an important mediator of Notch signaling, and its transcript activity triggers the expression of Notch target genes. Overactivation of Notch signaling in Sertoli cells strongly inhibits the expression of several Sertoli cell-expressed genes, including Gdnf and Cyp26b1 which are essential for the proper maintenance of spermatogonial stem cells, and induces premature differentiation and apoptosis of gonocytes Garcia et al, , 2014. Therefore, it is tempting to speculate that the RBPJ gene duplication in this interval is responsible for the congenital heart defects, limb anomalies, and hypogonadism of our patient.…”
Section: Discussionmentioning
confidence: 82%
“…Haploinsufficiency of the RBPJ gene causes Adams-Oliver syndrome 3, AOS3 (MIM 614814), a rare dominant genetic condition, characterized by aplasia cutis congenita, transverse terminal limb defects, cutis marmorata telangiectatica congenita, and cardiovascular malformations [Lin et al, 1998;Maniscalco et al, 2005;Snape et al, 2009;Algaze et al, 2013]. In addition, numerous studies indicate that Notch signaling in Sertoli cells is crucial for proper regulation of the testis stem cell niche essential for directing the population size and differentiation fate of spermatogonial stem cells [Kitadate et al, 2010;Garcia et al, , 2014. Dysregulation of spermatogonial stem cells causes infertility or germ cell hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that cells comprising the SSC niche produce signals (e.g., GDNF, KITL, RA, FGF2, CSF1, NOTCH2) which help instruct this balance by promoting either self-renewal or differentiation (Busada et al 2015a;Chen et al 2014Chen et al , 2016Dann et al 2008;Garcia et al 2014;He et al 2008;Ishii et al 2012;Kubota et al 2004;Meng et al 2000;Oatley et al 2006;Oatley et al 2007Oatley et al , 2009Ohta et al 2000;Schrans-Stassen et al 1999;Takashima et al 2015). It is well recognized that cells comprising the SSC niche produce signals (e.g., GDNF, KITL, RA, FGF2, CSF1, NOTCH2) which help instruct this balance by promoting either self-renewal or differentiation (Busada et al 2015a;Chen et al 2014Chen et al , 2016Dann et al 2008;Garcia et al 2014;He et al 2008;Ishii et al 2012;Kubota et al 2004;Meng et al 2000;Oatley et al 2006;Oatley et al 2007Oatley et al , 2009Ohta et al 2000;Schrans-Stassen et al 1999;Takashima et al 2015).…”
Section: Regulation Of Ssc Self-renewal: Instruction From the Nichementioning
confidence: 99%